Pengaruh Pemahaman Dan Peran Perangkat Desa Terhadap Akuntabilitas Pengelolaan Dana Desa (Studi Kasus Pada Desa Di Kecamatan Pinangsori Kabupaten Tapanuli Tengah) - Sahala Purba (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
This study serves to examine the effect of understanding and the role of village officials on the accountability of village fund management. The sample of this research is a village in Pinangsori District, Central Tapanuli Regency. The method in selecting the sample is the purposive sampling method in which the village head, village secretary, head of financial affairs, head of general affairs, head of government, head of welfare and hamlet head have a minimum education level of SMA/SLTA equivalent. The sample in this study were 35 respondents. The results of this study state that the role of village officials has a positive influence on the accountability of village fund management, while the understanding of village officials has no influence on the accountability of village fund management. This study has an Adjusted R Square (R2) of 0.277, which means that the dependent variable, namely the accountability of village fund management, can be explained by the understanding and role of village officials by 27.7%, while the remaining 72.3% is explained by other variables. not investigated in this study.